KECERDASAN EMOSIONAL SISWA YANG AKTIF MENGIKUTI KEGIATAN ROHIS SMA MUHAMMADIYAH 1 PEKANBARU - wahyuni, Fitri; Umari, Tri; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Emotional intelligence (EQ) is a person’s ability to accept, manage and control the emotions of himself and the people around him. This emotional intelligence refers to the feelings of someone who makes someone inclined to act. Spritual Islam (Rohis) is an organization strengthening and deepening religios teaching. Rohis includes activities carried out outside of face-to-face lessons. Where students who follow extracurricular will be higher emotional intelligence than students who do not follow extracurricular activities. This study aims to determine the emotional intelligence include self-awareness, self-regulation, motivation, emphaty and social skills. The method used in this research is descriptive quantitative. Based on the results of research that has been done on 30 subjects in SMA Muhammadiyah 1 Pekanbaru note that the emotional intelligence is 56,67%. Where can be reviewwed from the highest indicator include, motivation, self-awareness, and self-regulation. This means that students who have high emotional intelligence they feel happy to follow the activities of Rohis, a little temperament, and have a strong desire to continue to improve performance.Keyword : Emotional Intelligence, Active Student Rohis.